2007
DOI: 10.1016/j.envpol.2006.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of estrogenic effects in sewage and industrial wastewaters in Beijing, China

Abstract: Estrogenic activity in Beijing river water is attributed to direct discharges of untreated municipal and industrial wastewaters. AbstractEstrogenic potencies of the effluents or water samples from wastewater treatment plants (WWTPs), industries and hospitals and some receiving rivers in Beijing city were estimated by using a human estrogen receptor recombinant yeast assay. Estrogenic activity of industrial wastewaters was found to range from 0.1 to 13.3 ng EEQ/L and decreased to the range of 0.03e1.6 ng EEQ/L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 41 publications
0
46
0
1
Order By: Relevance
“…Consequently, monitoring influent and effluent steroid estrogen concentrations and assessing their fate in different areas and different WWTP treatment processes are essential. Previous reports have shown estrogenic activity in effluent from large sewage treatment plants in Beijing (Ma et al 2005(Ma et al , 2007 and revealed the presence of steroid estrogens in WWTP influent and effluent in China (Jin et al 2008;Chang et al 2011;Zhou et al 2011). However, studies on seasonal variation and the removal and degradation mechanism of steroid estrogens in WWTPs are absent in China.…”
Section: Introductionmentioning
confidence: 90%
“…Consequently, monitoring influent and effluent steroid estrogen concentrations and assessing their fate in different areas and different WWTP treatment processes are essential. Previous reports have shown estrogenic activity in effluent from large sewage treatment plants in Beijing (Ma et al 2005(Ma et al , 2007 and revealed the presence of steroid estrogens in WWTP influent and effluent in China (Jin et al 2008;Chang et al 2011;Zhou et al 2011). However, studies on seasonal variation and the removal and degradation mechanism of steroid estrogens in WWTPs are absent in China.…”
Section: Introductionmentioning
confidence: 90%
“…From an ecotoxicological view, the estrogenic effects of steroid estrogens on test animals have been observed in the range of 0.2-1 ng/l, which are lower than those commonly detected in aquatic environments Legler et al 2002;Zuo et al 2005;Campbell et al 2006;Labadie and Budzinski 2006;Zha et al 2008). Consequently, steroid estrogens in water environments may pose a significant threat to aquatic life or those depending on such water (Purdom et al 1994;Hansen et al 1998;Sun et al 2007;Ma et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, by chemical analysis approach alone, only limited chemical concentration information can be obtained from the analyzed wastewaters, with little understanding of potential adverse effects on the environment [12]. Fortunately, bioassays can integrate the effects of all pollutants and show the integrated activity of a whole effluent [14][15][16]. Therefore, in vitro bioassays combined with chemical analysis could provide better understanding of the risks of chemicals and potential impacts of industrial wastewaters on organisms in the environment [17,18].…”
Section: Introductionmentioning
confidence: 99%